(untitled) (NAU Journal of Technology and Vocational Education, 2024)
Poor academic achievement of students in building/woodwork trade in Oyo State government technical colleges as a result of defects in demonstration method of teaching prompted the researchers to adopt project method as an alternative means to effective teaching and a way of replacing the old one. Two research questions and two hypotheses were postulated in line with the stated objectives. Quasi-experimental research design was adopted for the study. A sample of 78 building/woodwork trade year III students drawn by purposive sampling technique from a population of 250 students in five government technical colleges was used for the study. The instrument for data collection was a Building/Woodwork Trade Achievement Test (BWTAT) validated by three experts. Test-retest method was used to obtained reliability coefficient value of 0.76 through Person product moment correlation coefficient. The study revealed that project teaching method was more effective than conventional method in enhancing students’ academic achievement in building/ woodwork trade. Also, it was found that project teaching method increases male academic achievement than female students in building/woodwork trade. Therefore, it was recommended that technical teachers should have workshop guidelines on how to use project method for practical skills on students. Also, technical teachers should ensure they plan their lessons with equal learning chances for both male and female students.